DEVELOPMENT STRATEGY OF KAMPUNG PRENEUR THROUGH CREATIVE ECONOMY WITH PENTA-HELIX METHOD (CASE STUDY ON KAMPUNG PRENEUR IN YOGYAKARTA CITY) - Niken Widyastuti; Krisna Mutiara Wati (Sean Institute, 2023)
Kampung Preneur is very inherent in the pattern of community empowerment which acts as a pancer (center) storefront as well as a business incubator based on four directions (values), namely global value, local wisdom, local supply chain and global marketing. The four directions are based on one pancer community development or community empowerment as the driver of the rural economy. The purpose of this research is to analyze the development of Preneur Village in Yogyakarta City through the creative economy and the pattern of strategies used for development through a SWOT analysis approach with the Penta-Helix model. Where the Penta-Helix or multi-stakeholder model where elements of the Government, academics, business entities or actors, communities or communities, and the media are united in coordinating and committing to developing the local potential of rural areas. Qualitative research method with descriptive approach. Descriptive research is research that guides researchers to explore and portray social situations thoroughly, broadly and in depth, where later surveys and interviews will be conducted on the actors involved in the Penta-Helix model how far the interaction patterns between the five actors (Academic, Business, Community, Government, and Media) by collaborating symbiotically mutualism in designing and developing a creative economy with an aggressive strategy, namely using strengths to take advantage of opportunities. The research results of the Penta-Helix concept of preneur villages in Yogyakarta City can realize the Village SDG's in achieving accelerated village economic recovery, food and energy security, welfare, and security stability.